Discharge planning handbook for healthcare top 10 secrets to unlocking a new revenue pipeline - Birjandi, Ali (CRC Press, 2009)
Hidden opportunities to improve profits in the healthcare industry abound in the area of discharge planning. This title shows hospital administrators and directors how they can tap into new revenue using the Six Sigma DMAIC model (Define, Measure, Analyze, Improve, and Control). It also includes a comprehensive case study.